2008
DOI: 10.1208/s12249-008-9164-3
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation by Spray Coagulation of Diltiazem HCl in Calcium Alginate-Coated Chitosan

Abstract: Abstract. The aim of this work was to develop a procedure for encapsulation of diltiazem HCl by spray coagulation. Factors affecting the formulations such as the effect of NaCl on the solubility of diltiazem in alginate solution, surface tension, pH, viscosity of the coagulation medium, and the effect of drug load on drug release were studied. The drug load was increased substantially from 10 up to 320 mg/mL by adding 1.2% w/v NaCl in 1% w/v alginate solution. More stable microcapsules were obtained at pH 4.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…In this case, the active agent, mostly depending on its solubility, is dissolved either in the polyanion solution (Sahasathian et al, 2010;Tapia et al, 2008) or in the chitosan solution (Dutta and Sahu, 2012;Kaur and Kaur, 2012). In this case, the active agent, mostly depending on its solubility, is dissolved either in the polyanion solution (Sahasathian et al, 2010;Tapia et al, 2008) or in the chitosan solution (Dutta and Sahu, 2012;Kaur and Kaur, 2012).…”
Section: Chitosan-based Pecs In Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the active agent, mostly depending on its solubility, is dissolved either in the polyanion solution (Sahasathian et al, 2010;Tapia et al, 2008) or in the chitosan solution (Dutta and Sahu, 2012;Kaur and Kaur, 2012). In this case, the active agent, mostly depending on its solubility, is dissolved either in the polyanion solution (Sahasathian et al, 2010;Tapia et al, 2008) or in the chitosan solution (Dutta and Sahu, 2012;Kaur and Kaur, 2012).…”
Section: Chitosan-based Pecs In Drug Deliverymentioning
confidence: 99%
“…The loading of small molecules in chitosan-alginate microcapsules and the release rate may depend on the ionic force (Tapia et al, 2008) and the pH (Lee et al, 1997) of the solutions where the reactions and microencapsulation occur. Loading of the antihypertensive agent diltiazem.HCl in chitosan-alginate microcapsules prepared by the spray coagulation method increased from 10 to 320 mg/mL by adding an appropriate quantity of NaCl to the alginate solution (Tapia et al, 2008).…”
Section: Small Moleculesmentioning
confidence: 99%
“…Each assay was done in triplicate. The dissolution data were analyzed according to Dobashi's model for fast release in acid and phosphate (14) and Weibull's model for prolonged release in water (16). From these models, the mean dissolution time, T 50 , was estimated.…”
Section: Drug Release Studiesmentioning
confidence: 99%
“…The smaller individual size of CaAlCS in acid medium has been described previously. It was found that the presence of chitosan restricts the penetration of the solvent into the core of calcium alginate and thus maintains a smaller size (14). In acid medium, the fast release of 5-ASA from the CaAl would be favored by the high solubility of the drug and because the alginate is in its unionized form so that the matrix would not suffer a swelling-erosion process.…”
Section: Drug Dissolution Behavior Of Microparticlesmentioning
confidence: 99%
See 1 more Smart Citation